(untitled) (Sociología y tecnociencia, 2013)
Migration research, which tends to focus on the low paying and exploitative nature of female migrants’ work, often neglects female skilled migration. Under-representation of the gender dimension is not only common in international migration research, but is also present in policies, development strategies and initiatives. This lack of acknowledgement also impedes, and continues to marginalise, the role of women in development, and further perpetuates disparities between the sexes. Overall, the focus on gender within the study of international migration and diaspora mobility studies remains inadequate. The methodology behind this article involved questionnaires and semi-structured in-depth interviews conducted with Ethiopian skilled and highly-skilled professionals residing in North America. Some temporary and permanent returnees were interviewed, including government officials, local NGOs and members of international organizations. The research sheds new light on the gender dimensions of the role of the diaspora in contributing to the re-shaping of Ethiopian society. The article explores aspects of ambiguity among gender roles in both North America and in Ethiopia. This article will explore these themes and also discuss the gender dimension of skilled migration and female diaspora mobility in the context of African development, specifically relating to Ethiopia. It will analyse the role of women in the realm of international skilled migration, in order to recognize and empower migrant women as agents of development and change.